District heat tracing of water and sewer lines in Kiruna, Sweden - Pericault, Youen; Hedström, Annelie; Dahl, Jan; Vesterlund, Mattias; Olsson, Göran (Luleå tekniska universitet, Arkitektur och vatten, 2016)
Godkänd; 2016; 20160125 (youper)